Determination of Magnetic Properties of Drugs and Balanced Wastes Based on the Fluorescence Resonance Energy Transfer (FRET) Phenomenon - Dina A Chusniyah; Djoko H. Santjojo; Chomsin S. Widodo (Natural B, Journal of Health and Environmental Sciences, 2014)
Along with population growth, the need for clean water is increasing. The availability of clean water is starting to decrease due to the decline in quality and quantity of water in the environment. Water quality degradation can be caused by water pollution from industrial waste disposal. One of the parameters to measure the level of pollution is the biochemical oxygen demand (BOD). Beside titration, biosensor method is a method developed to measure the BOD. The purpose of this study is to design a microorganism-based biosensor that can be used to measure levels of Biochemical Oxygen Demand (BOD5) using a microelectrode transducer with Pseudomonas putida and Pseudomonas fluorescents as bioreceptor on phenol wastes. BOD concentration was controlled by adding phenol in water with concentration of 0 mg/L, 50 mg/L, 100 mg/L, 150 mg/L, 200 mg/L and 250 mg/L. BOD concentration as measured by using titration method and developed biosensor. Experimental result shows that the potential of the biosensor linearly correlated to the concentration of BOD in water. Membrane surface area does not contribute any effect to the output potential of the biosensor. We can conclude that both Pseudomonas putida and Pseudomonas fluorescents can be use as material for measuring BOD concentration in water.